Effect of metakaolin replaced granulated blast furnace slag on fresh and early strength properties of geopolymer mortar - Huseien, G.; Mirza, J.; Ismail, Mohamed; Ghoshal, S.; Ariffin, M. (2016)
We report the effect of metakaolin (MK) substituted granulated blast furnace slag (GBFS) on the early strength of geopolymer mortars (GPMs) for potential repair applications. Such GPMs were prepared by activating MK (0-15%) replaced GBFS. Solution concentrations ratio of SiO2:Na2O were varied in the range of 1.08-1.26 to achieve appropriate geopolymerization. Various proportion of Na2O:dry binder (7, 8, 9, 11 and 13%) were used. The mass ratios of sodium silicate to sodium hydroxide (NS:NH) and the binder to fine aggregate (B:A) were fixed to 3.0 and 0.90, respectively. The mechanical properties of the synthesized GPMs were determined at ambient temperature after 24h of casting and curing. It is demonstrated that 5% of MK replaced GBFS with 1.16 of SiO2:Na2O and 0.40 of S:B achieved an early compressive strength as much as 47.84MPa at 24h. The bond strength results exhibited the prospect of such GPMs as suitable alternative repair material.